Microsoft SQL Server 2008 R2 Master Data Services : manage and maintain your organization's master data effectively with Microsoft SQL Server 2008 R2 Master Data Services /: manage and maintain your organization's master data effectively with Microsoft SQL Server 2008 R2 Master Data Services. (2011) - Unknown
No abstract available